The Role of Emotional Processes in Explaining the Link Between Severity of Childhood Maltreatment and Relationship Difficulties - McNeil, Julia (Journal of interpersonal violence, 2024)
Up to 32% of adults have experienced some form of childhood maltreatment (CM). Research has shown that these early childhood experiences are associated with a variety of interpersonal difficulties in adult sexual and romantic relationships. Polusny and Follette have suggested that these negative long-term effects are the result of emotional avoidance strategies that individuals use to cope with thoughts, feelings, and memories associated with CM. The present study tested this theorized mediational model with a sample of 150 participants, all of whom were currently in long-term relationships. Participants completed questionnaires designed to assess the severity of CM, fear of their own emotions, and a task designed to assess their accuracy at identifying emotions. Additionally, participants completed a variety of measures assessing the quality of their sexual and romantic relationships. These measures assessed their satisfaction, their communication, and the extent of problems in each domain. Our results showed that higher levels of CM were associated with lower satisfaction with communication and more problems in both the romantic and sexual domains. In regard to our mediational hypothesis, we found partial support showing that fear of one’s own emotions and emotion recognition mediated some of these associations. Our findings suggest that treatments targeting affective processes may be particularly important for helping victims of CM.